Calorie intake responses to macroeconomic adjustment - Briones, Roehlano M. (1996)
The paper characterizes the responses of household calorie intake to stabilization and structural adjustment. Using a model of calorie intake response derived from a food demand model of Philippine households, it shows that elasticities of total calorie intake with respect to prices and income in absolute terms tend to fall with income, implying an increasing vulnerability to malnourishment of lower income groups to adverse shocks. Then using a general equilibrium model of the Philippine economy, it shows that the effect of the structural adjustment program(specifically the 1988-1992 tariff reform program) is small but positive on calorie intake, with higher proportional increases in consumption of calorie sources for the lower income groups. The study indicates that growth policies probably involve no short-term trade-off with nutrient intake, whereas implementation of stabilization policies requires close integration with targeted programs on nutrition intervention and food price subsidies.
Keywords: Caloric content of foods; Food consumption